2016
DOI: 10.18869/acadpub.ijrr.14.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Impact of contrast agents on dose algorıthms of planning systems

Abstract: Background: Use of contrast agents (CAs) during CT simula on for treatment planing system leads to changes in electron density. In this study we aimed to inves gate the effect on calculated dose of various concentra ons of CAs on treatment planing systems in different dose calcula on algorithms. Materials and Methods: Contrast agent (0.769 mg/ml Iopromid) -water mixtures at concentra ons of 0%, 1%, 2%, 5% and 10% in total volume of 500 ml for each were made by using five iden cal balloons. Calcula ons were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…These studies can be grouped into two main categories: the first one is based on phantoms and mathematical models, the second is based on clinical CT images. Studies in the first category lean toward simulating clinical observations based on the amount of contrast material and beam energy; results generally tend to emphasize the apparent significant effect of contrast material rather than the clinical effect [13,16,17]. While studies in the second category generally place emphasis on clinical outcome and reported dose, differences were mostly within clinically acceptable limits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies can be grouped into two main categories: the first one is based on phantoms and mathematical models, the second is based on clinical CT images. Studies in the first category lean toward simulating clinical observations based on the amount of contrast material and beam energy; results generally tend to emphasize the apparent significant effect of contrast material rather than the clinical effect [13,16,17]. While studies in the second category generally place emphasis on clinical outcome and reported dose, differences were mostly within clinically acceptable limits.…”
Section: Discussionmentioning
confidence: 99%
“…Jing et al [20] concluded that oral contrast agents caused clinically significant changes in the dose calculations for the targets and critical structures. Rankine et al [13] reported significant dose discrepancy for critical structures, and Burridge et al [34] found a considerable increase in MU settings due to contrast agents presence in CCT images. The results in this study show that HU variations due to contrast materials were statistically significant (p-value < 0.05) for the majority of critical structures and target volumes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study, Izmirli et al investigated that the effect of calculated dose at various contrast medium concentrations in treatment planning systems for different dose calculation algorithms. 12 Izmirli et al reported that the dose difference for treatment plans with and without the contrast medium was within 2.2% at less than 2 mg ml −1 concentration. The contrast medium extraction method could be useful by using DECT images at 80 kV/135 kV for radiation treatment planning.…”
Section: Discussionmentioning
confidence: 99%